Association between Predatory Arthropods and Weeds on Sugarcane Plants - Devi, Mia Prastika; Rahardjo, Bambang Tri; Tarno, Hagus (Research Journal of Life Science, 2022)
While a large number of farmers in the tropics consider weeds to be just a nuisance, some weeds can potentially have benefits for cultivated crops. Weeds around cultivated plants can act as a biocide, soil improvement, and a food source for humans and animals, as well as a habitat for some insects. Based on the regression analysist, weed density has a relationship to the diversity of predatory arthropod species (R2= 0.026; P<0.001) and the abundance of individual predatory arthropods (R2= 0.010; P<0.001). Beneficial weeds around sugarcane plantations create mutually beneficial interactions. Weeds can be used as a place to live, reproduce, and produce nutrients for predatory arthropods. Research on the role of weeds against natural enemies from predators in sugarcane agroecosystems is also rarely studied. In this study, the focus was on the association of weeds with the diversity and abundance of predatory arthropods in the sugarcane agroecosystem.